Perlakuan Akuntansi Aset Tetap Pada Perusahaan Daerah Air Minum Kabupaten Kudus - Tentyadesty Enggar Panggalih; Didiek Susilo Tamtomo (Politeknik Negeri Semarang, 2018)
The goals of final report are to calculate and recognize fixed assets, record fixed assets and present, disclose the fixed assets of Kudus Disctrict water company. The method of writing used in this final report is description method and exposition methode. The description method is used to describe the general description of Kudus Disctrict water company and the exposition is used to explain the treatment of fixed assets at Kudus Disctrict watercompany. The result of this Final report is Fixed assets are recognized when the asset is ready for use at acquisition cost. Calculation of the acquisition price of fixed assets until December 31, 2016 amounting to Rp 126,734,497,850, the accumulated fixed assets up to December 31, 2016 amounting to Rp 49,116,678,669, and depreciation expense up to December 31, 2016, the recording of fixed assets In journal, ledger and subsidiaries ledger, and the presentation and disclosure of property and equipment to the Financial Statements